Variance and skewness of the multiplication gain distribution in uniform avalanche diodes - Zambon, P. (Frontiers in Physics, 2024)
We derived exact analytical expressions for the variance, the third central moment and the skewness of the multiplication gain distribution in uniform avalanche structures. The model assumes Poissonianity and locality of the ionization process and it is valid for arbitrary values of electron and hole ionization coefficients α and β, respectively, functions of the space coordinate.Expressions are also provided for the particular case where the ionization coefficients are related by a constant ratio k = β/α. The skewness is found to be always positive and greater than 2, therefore statistically relevant. Implications for spectral measurements of ionizing radiation are finally reviewed.